Physical Activity, Sedentary Time, and Obesity in an International Sample of Children. Issue 10 (October 2015) - KATZMARZYK, PETER T.; BARREIRA, TIAGO V.; BROYLES, STEPHANIE T.; CHAMPAGNE, CATHERINE M.; CHAPUT, JEAN-PHILIPPE; FOGELHOLM, MIKAEL; HU, GANG; JOHNSON, WILLIAM D.; KURIYAN, REBECCA; KURPAD, ANURA; LAMBERT, ESTELLE V.; MAHER, CAROL; et al.
ABSTRACT: Purpose: To determine the relationships between moderate-to-vigorous physical activity (MVPA), vigorous physical activity (VPA), sedentary time, and obesity in children from 12 countries representing a wide range of human development. Methods: The sample included 6539 children age 9–11 yr. Times in MVPA, VPA, and sedentary behaviors were assessed by accelerometry. The body mass index (BMI; kg·m −2 ) was used to classify children as obese based on z -scores (> +2 SD) from World Health Organization reference data. Results: The mean (SD) times spent in MVPA, VPA, and sedentary behavior were 60 (25) min·d −1, 18 (11) min·d −1, and 513 (69) min·d −1, respectively. The overall proportion of the sample that was obese ranged from 5.2% to 24.6% across sites. The odds ratios for obesity were significant for MVPA (0.49; 95% CI, 0.44–0.55), VPA (0.41; 0.37–0.46), and sedentary time (1.19; 1.08–1.30) in the overall sample. The associations of MVPA and VPA with obesity were significant in all 12 sites, whereas the association between sedentary time and obesity was significant in five of the 12 sites. There was a significant difference in BMI z -scores across tertiles of MVPA ( P < 0.001) but not across tertiles of sedentary time in a mutually adjusted model. The results of receiver operating characteristic curve analyses for obesity indicated that the optimal thresholds for MVPA (area under the curve [AUC], 0.64), VPA (AUC, 0.67) and sedentary behavior (AUC, 0.57) were 55 (95% CI, 50–64) min·d −1, 14 (11–16) min·d −1, and 482 (455–535) min·d −1, respectively. Conclusions: Greater MVPA and VPA were both associated with lower odds of obesity independent of sedentary behavior. Sedentary time was positively associated with obesity, but not independent of MVPA. Attaining at least 55 min·d −1 of MVPA is associated with lower obesity in this multinational sample of children, which supports current guidelines.